GAMBARAN MAID CAFÉ DALAM ANIME KAICHOU WA MAID-SAMA! KARYA SAKURAI HIROAKI DENGAN PENDEKATAN POP CULTURE - AINIE, NUR (Jurnal Ilmiah Mahasiswa FIB, 2014)
Maid café  is one of the popular culture phenomenon of Japan.  This phenomenon appear in Japan in 2000th. Maid café’s popularity occupies the third place after the  anime, comics, and games. Maid cafes are not only popular in Japan, but the popularity also venturing abroad such as America, Hong Kong, Taiwan, and Singapore.  Not only popular in real life, in  the animation  film  , maid café was so popular  too.  Anime  is the Japanese term for animation with various types  of stories.  Anime  that will be used in this  study  is  Kaichou  Wa Maid-sama!  by Director Hiroaki Sakurai. This  study  uses    pop culture approach to  the service, cosplay, and events aspects at the maid café. This aspect is used to determine the reason for the Maid Latte’s café  is so popular in the  anime Kaichou wa Maid-sama!.  The results of this  research indicate the service, cosplay, and events aspects that make the Maid Latte become popular. Maid Latte is not only favored by the otaku, but also loved by the ordinary people In addition,  recommended  to use the same anime  for  further  reseach, but used the concept of gambaru  to find out    the never give up attitude of Japanese society that pictured through the main female character.  Keywords : Maid Cafe, Pop Culture, Kaichou Wa Maid-sama!